A Paradigmatic Analysis of Digital Application Marketplaces. (September 2015) - Ghazawneh, Ahmad; Henfridsson, Ola
This paper offers a paradigmatic analysis of digital application marketplaces for advancing information systems research on digital platforms and ecosystems. We refer to the notion of digital application marketplace, colloquially called 'appstores, ' as a platform component that offers a venue for exchanging applications between developers and end users belonging to a single or multiple ecosystems. Such marketplaces exhibit diversity in features and assumptions, and we propose that examining this diversity, and its ideal types, will help us to further understand the relationship between application marketplaces, platforms, and platform ecosystems. To this end, we generate a typology that distinguishes four kinds of digital application marketplaces: closed, censored, focused, and open marketplaces. The paper also offers implications for actors wishing to make informed decisions about their relationship to a particular digital application marketplace.